Pengaruh pendidikan kesehatan terhadap pengetahuan tentang Perilaku Hidup Bersih dan Sehat (PHBS) pada siswa kelas V MIN 1 Lombok Tengah - Romadonika, Fitri; Nursukma Purqoti, Dewi; Wasliah, Indah; Assuaro Soliha, Siti (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2021)
Clean and Healthy Behavior in schools is the initial order to create healthy and quality human resources for the progress of the nation and state. At the age of elementary school children need health supervision. School children are one of the most vulnerable groups to health problems due to environmental factors and poor lifestyle. This study discusses health education on knowledge about Clean and Healthy Behavior for students in class V MIN 1 Central Lombok. This study used an experimental research design with a quasi-experimental design using one pre-post grub test, the number of students was 146 students and a sample of 30 students with a sampling technique using purposive sampling. Data analysis used Wilcoxon signed ranks test. Based on the results of statistical tests using the Wilcoxon signed ranks test the knowledge value before and after the intervention p value 0.000 (p <alpha) while the observation results before and after the intervention obtained p value 0.000 (p <alpha), it can be concl uded that there is a significant influenAce in providing education health to knowledge about Clean and Healthy Behavior on students. Student behavior related to Clean and Healthy Behavior (PHBS) is very important to be improved, because at that age it is very susceptible to disease.